2017
DOI: 10.1371/journal.pone.0186878
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of pten knockout medaka with transcription activator–like effector nucleases (TALENs) as a model of PTEN deficiency disease

Abstract: Phosphatase and tensin homolog (PTEN) is a lipid and protein phosphatase that antagonizes signaling by the phosphatidylinositol 3-kinase (PI3K)–AKT signaling pathway. The PTEN gene is a major tumor suppressor, with mutations of this gene occurring frequently in tumors of humans and mice. We have now developed mutant medaka deficient in PTEN with the use of transcription activator–like effector nuclease (TALEN) technology. Medaka possesses two pten genes, ptena and ptenb, similar to zebrafish. We established 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another miRNA, miR-21, could decrease autophagy by down-regulating PTEN in mesangial cells [ 37 ]. In fish, it has been reported that zebrafish PTEN deficiency induced the activation of PI3K/mTOR pathway and AKT, which affected embryo and tissue development [ 38 , 41 ]; madaka PTEN knockout also upregulated PI3K/AKT signaling, which led to abnormal embryo development [ 42 ]. In the present study, we found that compared with human and mouse PTEN, fish PTEN homologs are highly conserved in sequence and structure, and, in flounder, PoPTEN was constitutively expressed in a wide range of tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another miRNA, miR-21, could decrease autophagy by down-regulating PTEN in mesangial cells [ 37 ]. In fish, it has been reported that zebrafish PTEN deficiency induced the activation of PI3K/mTOR pathway and AKT, which affected embryo and tissue development [ 38 , 41 ]; madaka PTEN knockout also upregulated PI3K/AKT signaling, which led to abnormal embryo development [ 42 ]. In the present study, we found that compared with human and mouse PTEN, fish PTEN homologs are highly conserved in sequence and structure, and, in flounder, PoPTEN was constitutively expressed in a wide range of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, studies on PTEN have been documented mainly in zebrafish, in which it was shown that PTEN played an important role in embryonic development, caudal fin-fold regeneration, tumorigenesis, hematopoiesis, and myelocyte migration [ 38 , 39 , 40 , 41 ]. In medaka, PTEN was also shown to be involved in embryo development [ 42 ].…”
Section: Introductionmentioning
confidence: 99%